Peran Cash Holding dan Rasio Finansial Terhadap Penilaian Kinerja Perusahaan Sektor Non-Cylicals di Indonesia - Siti Dwi Arini; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study is motivated by persistent inconsistencies in research findings (a research gap) regarding the factors influencing corporate performance, particularly within the non-cyclical consumer goods sector in Indonesia. The study aims to analyze the impact of cash holdings, profitability, leverage, sales growth, and cash flow volatility on corporate performance, as proxied by Tobin's Q. The subjects of the study are non-cyclical consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A quantitative approach is employed, utilizing secondary data obtained from financial statements and annual reports accessed via the official IDX website. A total sampling technique was used; consequently, all companies meeting the research criteria were included in the sample, resulting in 288 observations over the study period. Data analysis was conducted using the Generalized Least Squares (GLS) method with the aid of Stata MP 17 software. This study is expected to provide empirical evidence regarding the influence of cash holdings, profitability, leverage, sales growth, and cash flow volatility on corporate performance, thereby contributing to the development of literature in the field of corporate finance. Furthermore, the findings are expected to serve as a reference for corporate management in formulating financial policies and for investors in evaluating company prospects as a basis for investment decision-making.